COMPREHENSIVE INFLUENCE ANALYSIS OF ELDERLY HEALTH PROMOTION MODEL BASED ON THEORY OF PLANNED BEHAVIOR IN PANTAI LABU DISTRICT, DELI SERDANG - Masdalifa Pasaribu (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
on the Theory of Planned Behavior (TPB). This study uses a cross-sectional design involving 333 randomly selected elderly respondents. Data were collected through questionnaires that included the components of the SDGs: attitudes towards behavior, subjective norms, and perception of behavior control. The results showed that all components of the SDGs had a significant effect on health behavior intentions, with attitudes towards behavior having the greatest influence (regression coefficient 0.45, p < 0.01), followed by subjective norms (0.30, p < 0.05) and perception of behavior control (0.25, p < 0.05). Although the intention to behave healthily is high (60%), only a subset of older people report consistent actual health behaviors, suggesting a gap between intention and action. Inhibiting factors such as physical limitations, poor access to health services, and inadequate social support were identified as major barriers. To address this gap, a comprehensive intervention approach is recommended through health education, strengthening social support, and improving service accessibility. In conclusion, the health promotion model based on the SDGs is effective in predicting the intention of the health behavior of the elderly and can be applied in health promotion programs in other regions.